1992
DOI: 10.1190/1.1443259
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic borehole fields in a layered, dipping‐bed environment with invasion

Abstract: Electromagnetic modeling of an induction sonde (1–100 kHz) in a dipping‐bed environment is a 3-D problem. The capability for such an analysis is necessary for interpretation of oil‐well logs in offshore environments where most holes are deviated. 3-D geometrical effects require vector field analysis. The method accounts for transverse magnetic mode (TM) coupling arising from surface charges deposited by eddy currents passing through bed boundaries. If borehole and invasion effects are included, the only availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…6a shows that the apparent thickness of the bed of interest becomes large with the dipping angle, and the curve amplitude becomes large, too. Meanwhile, the so-called "polarization angle" begins to emerge on the high-angle curves, which is mainly due to the accumulated surface charge at the formation boundaries [22] . In Figs.…”
Section: Conductivity Averaging Formulamentioning
confidence: 99%
“…6a shows that the apparent thickness of the bed of interest becomes large with the dipping angle, and the curve amplitude becomes large, too. Meanwhile, the so-called "polarization angle" begins to emerge on the high-angle curves, which is mainly due to the accumulated surface charge at the formation boundaries [22] . In Figs.…”
Section: Conductivity Averaging Formulamentioning
confidence: 99%
“…To this end, we will formulate the integral equation in (6) in the oblique (nonorthogonal) basis. Before discussing the transformation of the integral equation, we first write it as (11) where the vector is given by (12) in which the normalized vector potential is given by (13) The scalar Green function is given by (14) III. TRANSFORMATION PROCEDURE As shown in Fig.…”
Section: Basic Equations and Integral Representationsmentioning
confidence: 99%
“…Eigenfunction solutions to dipping-bed induction response are given by Hardman and Shen [10], Anderson et al [4], and Gianzero and Su [9]. The 3-D forward modeling of the induction response is given by Howard and Chew [11] and Anderson et al [5]. A one-dimensional (1-D) inversion method with dip is given by Minerbo [14].…”
Section: Introductionmentioning
confidence: 99%
“…Kaufman & Keller (1989) observed that the distance between "horns" is equal to the bed thickness plus the coil spacing. Howard & Chew (1992) showed theoretically, and Carvalho & Verma (1994) showed experimentally, through test tank measurements, that these oscillations on the logs are damped if the presence of the borehole and invasion are taken into account. Figure 10 shows the vertical profiles of the (a) coaxial and (b) coplanar arrays to an inclined bed sequence or a deviated borehole.…”
Section: Vertical Investigationsmentioning
confidence: 99%